Fiskal Peran Kebijakan Fiskal dan Moneter dalam Menjaga Stabilitas Ekonomi Makro - Fatrisia agustina wm Maya rani; Daniati Ilham; Desy Kurniawati; M. Yusuf Bahtiar (Faculty of Economic an Business Wijaya Kusuma Surabaya University, 2026)
Macroeconomic stability is a crucial pillar for maintaining a nation’s well-being, characterized by controlled inflation, low unemployment, sustainable economic growth, and price stability. The government and monetary authorities play a vital role in upholding this stability through fiscal and monetary policies. Fiscal policy manages government expenditure and revenue, whereas monetary policy—conducted by Bank Indonesia—focuses on regulating the money supply and interest rates. Synergy between these two policies is essential; expansive fiscal policy without appropriate monetary support can trigger inflation, while tight monetary policy during a recession can exacerbate economic contraction. This study employs a qualitative methods utilizing library research approach. This approach was selected because the primary objective is to explore and analyze the roles of fiscal and monetary policies in supporting macroeconomic stability. The findings indicate that coordination between fiscal and monetary policies was particularly significant during the COVID-19 pandemic, involving fiscal stimulus and interest rate cuts to stabilize the economy. When the economy weakens, the government implements expansive fiscal policy supported by accommodative monetary policy—such as low interest rates—to boost consumption and investment. Conversely, during periods of high inflation, a combination of tight fiscal policy and contractionary monetary policy can reduce aggregate demand and ensure price stability. Achieving this balance is critical for realizing sustainable macroeconomic goals, such as stable economic growth, controlled inflation, and low unemployment.